Profit Over Paradise: Exposing the Unsustainable Trajectory of Foreign Property in Canggu's Tourism Development - Dananjaya, Ahmad Ghazy (Graduate School, Universitas Brawijaya, 2025)
This study examines the ethical implications of foreign property dominance in Canggu, Bali, following the post-pandemic surge in digital nomads. Using a mixed-method approach involving 400 respondents, the research analyzes the impact of this demographic shift on social inequality and environmental integrity. The results demonstrate a strong correlation between foreign property expansion and widening social gaps. Findings reveal that local residents perceive significantly higher environmental degradation compared to the expatriate population. Specifically, the